Fuel-saving device rod electrode based on gasoline for fuel car - Siti Haifullia, Ayob (2010)
This final year project is about fuel-saving device on gasoline that are design to help the user on how to save the gasoline for car. The objective of this project is to design and experiment fuel-saving device rod electrode based on gasoline fuel car by using electrolysis method. The plastic container is used as the devices of this project where are functional as a method to collect the hydrogen gas to flow to the manifold of the car. The hydrogen gas is the device for the combustion in the engine of the car. It also as the device to help users in reducing uses of fuel for car. The circuit is formed to show how the hydrogen gas is produced. The circuit is build to show by using the electrolysis, the hydrogen gas can be produced and supplied into the manifold of the car. The circuit firstly is set up by tied the both of the stainless steel with the coil. It is function as the electrode in the plastic container which is cathode (-) and anode (+). Then the circuit is tested with the battery water mixed with sodium bicarbonate to test whether the stainless steel can produce bubble that is the hydrogen gas. Then, the production of hydrogen gas will flow through the tube to the manifold of the eddy current dynamometer. To get the result from this experiment, the eddy current dynamometer is used that is speed versus time. The result will be interpreted by the eddy current dynamometer readings that are discussed and presented. A conclusion on experimented project are presented and the problem faced are discussed.